The Educational Ideas of KH. Muhammad ‎Syamsul Arifin and Their Relevance to Modern ‎Education: From 1980 to 2021‎ - Mukit, Abdul (TADRIS: Jurnal Pendidikan Islam, 2023)
The objective of this research is to uncover the educational ideas presented by Kiai Muhammad and their consistent application in LPI Darul Ulum Pondok Banyuanyar Pesantren Pamekasan, which is one of Indonesia’s oldest Pesantrens, from the year 1980 to 2021. Additionally, the aim is to explore the significance of these ideas in the context of contemporary education. This study involves qualitative research using library and content analysis as an analysis technique to examine both primary and secondary data sources. The Primary data sources come from the written works of Kiai Muhammad, namely the book "Kalam Hikmah" while the secondary data sources are gathered from other relevant sources. The study reveals that Kiai Muhammad rendered 41 years of education service from 1980-2021. During this period, he accomplished remarkable feats by establishing Pesantren and formal educational institutions ranging from preschool up to college level. These institutions have proliferated both in the number of students and quality of education, attaining several recognitions and accolades at various levels. The foundation of Kiai Muhammad’s educational work was based on two key concepts: nationality and science. The outcomes of these two ideas hold great significance for the current educational criteria established by the government, specifically, the 8 Standard Pendidikan Nasional (Eight National Educational Standards) that encompass aspects such as content, process, graduate competence, educators and staff, facilities and infrastructure, management, financing, and evaluation.